Geochemical and VLF-LF radio precursors of strong earthquakes: a review. - Biagi, P; ERMINI, ANITA (Masashi Hayakawa, 2013)
Results obtained by the authors during many years of observations related to hydro-geochemical parameters and LF/VLF radio signals are presented. Firstly, the analysis carried out for more than ten years on the ions and gases content data collected from the groundwater of six deep wells and two natural springs in the southern area of the Kamchatka peninsula (Russia) is reported. The following general statements can be made: a) middle-term precursors could be observed during the preparatory phase of earthquakes with M (magnitude) around 7.0 and larger, located at distances less than 100-150 km from the measurement site; b) for larger distances, short-term precursors could be observed on the occasion of large but very shallow earthquakes and probably, in such cases, the dissolved gases are parameters more sensitive than the ions; c) on the occasion of large earthquakes, post-seismic effects can be observed; d) all the previous effects do not appear at each measurement site of a hydro-geochemical network and it means that they are related to some local phenomenology connected with the underground structural situation; e) long-term (some years) precursors could appear at each measurement site of a hydro-geochemical network. In such a case, probably a great increase of stress must be claimed and, as precursors, the variations could be related to more than only one large earthquake. The mentioned results were obtained in Kamchatka, that is an active margin where the Pacific plate subducts beneath the North American and Eurasia plate. In any case, they should represent the general behavior of the hydro-geochemical parameters in connection with the seismic activity. As concerns the LF and VLF radio signals, the results are reported obtained with the VLF and LF receivers located in Bari (south Italy) and in Assergi (central Italy), respectively. The following general statements can be made: a) a good possibility exists that the earthquakes with M≥4.3 can produce some decrease in the intensity of the VLF radio signals, ...